KONSEP SEKOLAH RAKYAT DALAM PERSPEKTIF KI HAJAR DEWANTARA - Ahmad Baidowi; Nur Ahyat; Mohammad Fahrudi Noer (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2025)
Abstract This article explores the concept of the People's School based on the views of Ki Hajar Dewantara, a nationalist educational figure who founded Taman Siswa as a form of resistance to the colonial education system. Using qualitative descriptive methods and literature reviews, this study presents several important educational principles, such as the "Among" system, the concept of "Tri Pusat Pendidikan," and the philosophy of "Ing Ngarsa Song Tuladha, Ing Madya Mangun Karsa, Tut Woori Handayani." The findings of this study indicate that the idea of ​​Ki Hajar Dewantara's People's School remains relevant in shaping the personalities of independent, creative, educated, and responsible students. Furthermore, its values ​​can be applied in today's educational context, including the implementation of the Merdeka Curriculum and the challenges of education in the era of Society 5.0. Keywords: KI Hajar Dewantara, People's School, Among System, Independent Curriculum character education.